2017
DOI: 10.1371/journal.pone.0182203
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the preferences for involvement in medical decision making among patients with mental disorders

Abstract: BackgroundThe involvement of patients in medical decision making has been investigated widely in somatic diseases. However, little is known about the preferences for involvement and variables that could predict these preferences in patients with mental disorders.ObjectiveThis study aims to determine what roles mentally ill patients actually want to assume when making medical decisions and to identify the variables that could predict this role, including patients’ self-efficacy.MethodDemographic and clinical da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 60 publications
(90 reference statements)
2
12
3
Order By: Relevance
“…In line with existing research, 19 25 the majority of the participants interviewed in our study generally prefer a collaborative role regarding medical decisions. Patients wanted to be involved in the decision-making process prior to their current inpatient treatment and reported high information needs regarding treatment options in order to feel empowered to participate adequately in the decision for a certain treatment setting.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In line with existing research, 19 25 the majority of the participants interviewed in our study generally prefer a collaborative role regarding medical decisions. Patients wanted to be involved in the decision-making process prior to their current inpatient treatment and reported high information needs regarding treatment options in order to feel empowered to participate adequately in the decision for a certain treatment setting.…”
Section: Discussionsupporting
confidence: 85%
“… 18 Furthermore, the majority of patients with mental disorders prefer to be involved in treatment decision-making. 19 25 Although there is international consensus about the importance of SDM, 11 it is not yet widely implemented. 11 , 26 28 …”
Section: Introductionmentioning
confidence: 99%
“…The recent MAGIC study explored how shared decision-making could be embedded within the UK NHS, and identified many challenges. These include misplaced confidence amongst staff about their current practice, a perceived lack of tools to support shared decision-making and inaccurate assumptions about patients’ preferences [ 16 , 17 ]. MAGIC examined a number of clinical contexts, but excluded mental health, where shared decision-making faces particular challenges, reflecting a unique history founded on concepts of containment and coercion [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because of their fatalistic perspective, it was impossible to motivate this type for methods such as pleasant activations or other techniques of problem solving (35). There are further similarities to a quantitative study of Michaelis et al (36) who described types of people with a mental illness and their preferences on shared decision-making. They differentiate between autonomous, collaborative, and passive types in terms of different predictive values.…”
Section: Types Of Utilizationmentioning
confidence: 97%
“…They differentiate between autonomous, collaborative, and passive types in terms of different predictive values. Participants with a high burden of depressive symptoms and low perceived selfefficacy withdrew into a passive treatment role (36). De Smet et al (37) described this phenomenon as "being stuck between knowing vs.…”
Section: Types Of Utilizationmentioning
confidence: 99%